Accounting for Brazil's growth experience: 1940-2002 - Edmar Lisboa Bacha; Régis Bonelli (Institute for Applied Economic Research (ipea), 2015)
This paper is devoted to a quantitative assessment of Brazil's long-term growth experience. The analysis herein shows that savings alone do not explain the growth slump after 1980. Our explanation centers on the evolution of the output-capital ratio and on changes in the relative price of investment goods. A lower degree of capacity utilization also helps to elucidate Brazil's mediocre growth performance since 1980. Decadal decompositions of capital stock and GDP growth highlight the factors accounting for Brazil's growth in particular sub-periods.
Keywords: 330